Fuel treatment barrier allocation using a kriging metamodel (2016)
Efficient wildfire risk reduction policies have turned into a main priority for many fire departments in the globe. The preservation of the current reserves includes the consideration that we must incur in economic expenses in order to reduce the environmental cost of these disasters. This paper presents a methodology for developing fuel control policies that attempt to strategically reduce the expected damages caused by probable fires. We present an metamodel that optimizes the fuel control policy by allocating barriers in the forest. These allocation is done by using a black box algorithm based in a kriging metamodel for simulation based optimization. We tested Our algorithm in the allocation of the barriers a forest reserve in Bogotá, Colombia having a considerable reduction in the sim of expected fires, considering the size of the reserve